End User Response to an Event Detection and Route Reconstruction Security System Prototype for use in Airports and Public Transport Hubs - O'MAHONY, MARGARET (My University, 2016)
Video surveillance is ex tensively used in many countries for security purposes, contributing to effective prevention, detection, and/or prosecution of crime and terrorism. Although its contribution to security is not under de bate, its effect on the privacy rights of citizens has been the subject of much controversy. This paper reports the results of research which examined the potential use of new security technologies in an airport and a major public transport hub . The resear ch aimed to consider both the security and privacy implications of new security technologies, specifically closed circuit television (CCTV) with automatic event detection, alerts, and route reconstruction (to determine the route taken by a suspicious perso n in advance of a detected incident ) . The system also allows for the deletion of any footage not associated with the detected ev ents or reconstructed routes, when that footage was considered not relevant to security. Interviews and technology demonstratio ns were conducted with employees of two transport organisations, the airport operator of Linate and Malpensa A irport s in Milan in Italy, SEA, and the Spanish railway operator , Renfe Operadora. The main findings are that, w hile facets of the system appeal to the transport org anisations, changes would need to be made in order for it to be implementable. Particularly, the respondents pointed to the early deletion of the non - security relevant footage as an issue due to legal requirements placed on them.
Procs of the Annual Meeting of the Transportation Resarch Board, National Academy of Sciences,
PUBLISHED
Washington D.C.
Keywords: Smart & Sustainable Planet; Transport